PERLINDUNGAN KONSUMEN PENGGUNA LAYANAN INTERNET BOLT DAN BOLT HOME YANG DICABUT IZINNYA OLEH KEMENTERIAN KOMUNIKASI DAN INFORMATIKA TAHUN 2018 - Fivhi Indah Sari; Susanti Adi Nugroho (Fakultas Hukum Universitas Tarumanagara, 2019)
Many internet service providers are not compliant to pay frequency fees to the state so that the Ministry of Communication and Informatics closes PT. Internux which is a subsidiary of PT. First Media is a banned in Lippo Group. The closure resulted in Bolt and Bolt Home consumers not getting internet access so that problems arose 1. How to protect consumer rights for Bolt and Bolt Home internet service customers PT. Internux after revocation of permission by Kominfo? 2. What is the responsibility of the business actor for consumers of Bolt and Bolt Home internet service customers? The method used is the normative legal method. Bolt and Bolt Home consumers only get preventive protection by deactivating top up payment services in order to avoid greater losses for consumers, while repressive protection is not found in this case. The form of responsibility of PT. Internux to consumers based on the provisions of Article 19 Paragraphs (1) and (2) must provide compensation equivalent to the price of the quota package in accordance with the initial agreement agreed with the refund mechanism and provide diversion offer services to other providers. The Ministry of Communication and Information must conduct strict supervision of internet service companies and for consumers to be selective and smart in choosing internet service company providers.